The half-Space Model Problem for Compressible Fluid Flow - Sri Maryani; Lukman B Nugroho; Agus Sugandha; Bambang H Guswanto (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2021)
In this paper we consider the solution formula for Stokes equation system without surface tension in half-space. More precisely, we deal with the solution of velocity and density for the model problem. This result is the basic step to estimate the solution operator of the model problem. We investigate the solution operator for the model problem in N-Dimensional Euclidean space (N>=2)In this paper we consider the solution formula for Stokes equation system without surface tension in half-space. More precisely, we deal with the solution of velocity and density for the model problem. This result is the basic step to estimate the solution operator of the model problem. We investigate the solution operator for the model problem in N-Dimensional Euclidean space ()